Institutions for Asian integration: Innovation and reform - Giovanni Capannelli; See Seng Tan (Asian Development Bank Institute (ADBI), 2012)
The formation of regional production networks in East Asia has occurred mainly through market forces, without much help from regional institutions in promoting the creation of a single Asian market. While this approach has served the region well in the past, the drastic changes experienced since the 2008 - 2009 financial crisis and the challenges Asian countries are facing - rowing inequalities and competition, on the one hand, and enhanced threats to the environment and people's health on the other - have rendered more urgent the need for intergovernmental cooperation at global and regional levels. Asia's institutions for regionalism need strengthening through reform and innovation such as better governance and resourcing, greater and more effective participation and delegation of powers, overall streamlining of regional architecture, including the phasing out of outdated or irrelevant institutions and, where needed, the creation of new ones. Ultimately, given its rootedness in regional order, institutional efficacy is a function of the ability and willingness of its members, especially influential stakeholders, to collaborate.
Keywords: F15; F55; F59; 330; asian integration; asian institutions; regional production networks; east asia; single asian market; intergovernmental cooperation; Regionale Wirtschaftsintegration; Internationale Zusammenarbeit; Institutionelle Infrastruktur; Asien